ACCURACY ANALYSIS OF 3D COORDINATES FROM TERRESTRIAL LASER SCANNER (TLS) AND AIRBORNE LASER SCANNING (ALS) MEASUREMENTS (CASE STUDY: TRANSMISSION TOWER) - Prasetyo, Friski Putra; Kurniawan, Akbar; Dhiaurrahman, Antony Rafie; Setiawan, Fabian Saiadin (Elipsoida : Jurnal Geodesi dan Geomatika, 2025)
Transmission towers on high-voltage power lines serve as supporting structures for electrical conductors and insulators, requiring routine maintenance to ensure safety and reliability. This study aims to analyze the 3D coordinates of transmission towers using Terrestrial Laser Scanner (TLS) and Airborne Laser Scanning (ALS) methods. The calculation of the Root Mean Square Error (RMSE) against Total Station (TS) measurements showed that TLS achieved higher accuracy, with an RMSE of 0.0037 m, compared to ALS at 0.0136 m. Statistical testing using the t-distribution on 21 data points showed that the t-values for TLS and ALS were 1.967255 and -0.385437, respectively, both of which fall within the critical value range at a 5% significance level. It was therefore concluded that there was no significant difference compared to the Total Station (TS) measurements. The confidence interval analysis at a 95% confidence level indicated that 95% of the TLS data and 61% of the ALS data fell within the acceptable range. In terms of visualization, TLS produced a denser and precise point cloud with texture details, while ALS excelled in point cloud color representation. Each method has its advantages, with TLS being superior in detailed accuracy and ALS being efficient for large-area data acquisition. Keywords: Airborne Laser Scanning, Point Cloud, Terrestrial Laser Scanner, Transmission Tower